Choice of Law in International Contracts Based on the Hague Principles 2015: Indonesian Positive Law Perspective - Geofani Lingga Meryadinata; Shihaf Ismi Salman Najib; Ahmad Bastomi (JUSTISI, 2025)
The study aims to examine the principle of choice of law in The Hague Principles 2015, assess the application of choice of law and forum clauses in international contract disputes, and evaluate the relevance and obstacles to its application in Indonesian law to encourage harmonization and legal certainty in cross-border transactions. This research method used a normative legal approach through a literature study with three approaches: statute, case, and comparative. The focus is on applying The Hague Principles 2015 on the choice of law in international contracts and its relevance to Indonesian positive law to strengthen legal certainty and the parties' autonomy. The Novelty this study lies in the study of the potential adoption of THP 2015 in the Indonesian legal system, which until now has not officially recognized these principles. In addition, this study discusses the challenges of implementing legal options and forum options in national law and analyzes real cases of international contract disputes. The study results show that the principle of choice of law in The Hague Principles 2015 upholds the parties' autonomy. However, Indonesian law has not optimally accommodated this principle, causing uncertainty in applying choice of law and forum clauses in international contracts involving national jurisdictions. The conclusions of the Hague Principles 2015 affirm party autonomy in international contracts, allowing freedom to choose the applicable law. Though non-binding, they influence legal interpretation globally. Integration into Indonesia's legal system is recommended to enhance legal certainty, support cross-border trade, and guide judges, practitioners, and scholars in resolving international contract disputes.